Acute Mental Discomfort Associated with Suicide Behavior in a Clinical Sample of Patients with Affective Disorders: Ascertaining Critical Variables Using Artificial Intelligence Tools - Morales, Susana; Barros, Jorge; Echávarri, Orietta; García, Fabián; Osses, Alex; Moya, Claudia; Maino, María Paz; Fischman, Ronit; Núñez, Catalina; Szmulewicz, Tita; Tomicic, Alemka (Frontiers in Psychiatry, 2017)
In efforts to develop reliable methods to detect the likelihood of impending suicidal behaviors, we have proposed the following: Objective: to gain a deeper understanding of the state of suicide risk by determining the combination of variables that distinguishes between groups with and without suicide risk. Method: A study involving 707 patients consulting for mental health issues in three Health Centers in Greater Santiago, Chile. Using 345 variables, an analysis was carried out with artificial intelligence tools, CRISP-DM processes and Decision Tree techniques. The basic algorithm was top-down, and the most suitable division produced by the tree was selected by using the lowest Gini index as a criterion, and by looping it until the condition of belonging to the group with suicidal behavior was fulfilled. Results: Four trees distinguishing the groups were obtained, of which the elements of one were analyzed in greater detail, since this tree included both clinical and personality variables. This specific tree consists of six nodes without suicide risk and eight nodes with suicide risk (Tree decision 01, Accuracy 0.674, Precision 0.652, Recall 0.678, Specificity 0.670, F measure 0.665, ROC AUC73.35%; Tree decision 02, Accuracy 0.669, Precision 0.642, Recall 0.694, Specificity 0.647, F measure 0.667, ROC AUC68.91%; Tree decision 03, Accuracy 0.681, Precision 0.675, Recall 0.638, Specificity 0.721, F measure, 0.656, ROC AUC65.86 %; Tree decision 04, Accuracy 0.714, Precision 0.734, Recall 0.628, Specificity 0.792, F measure 0.677,ROC AUC58.85%). Conclusion: This study defines interactions among a group of variable associated with suicidal ideation and behavior. By using these variables, it may be possible to create a quick and easy-to-use tool. As such, psychotherapeutic interventions could be designed to mitigate the impact of these variables on the emotional state of individuals, thereby reducing eventual risk of suicide. Such interventions may reinforce psychological wellbeing, feelings of self-worth and reasons for living, for each individual in certain groups of patients.